Fecal microbiota transplantation for ulcerative colitis - Katsuyoshi Matsuoka (Immunological Medicine, 2021)
Altered abundance and composition of the gut microbiota, i.e., dysbiosis, is reported to be involved in the pathogenesis of various diseases including not only gastrointestinal diseases but also metabolic, neurological, and autoimmune disorders. Fecal microbiota transplantation (FMT) aims to correct dysbiosis by administrating feces collected from donors and thus treat the underlying disease. Ulcerative colitis (UC) is a disease characterized by chronic inflammation in the large intestine. Patients with UC have been reported to have dysbiosis, and more specifically, reduced diversity and abundance of the gut microbiota. FMT has been tried as a treatment for UC. Favorable effects of FMT on UC had been reported in case reports or case series. Recently, four randomized controlled trials of FMT for UC were published. Three of the four studies reported that FMT was more effective than control treatment. Thus, FMT is considered as a promising treatment for UC; however, there are many issues to solve before FMT can become a standard therapy for UC including donor selection, administration routes, frequencies, easy-to-administer formulation development, and optimal patient population.